Ukama Ustawi: Scaling Fund Report - Kihoro, Esther; Buono, Nicoletta; Mudereri, B.; Borus, D.; Gatto, Marcel; Vyas, Shalika (International Livestock Research Institute, 2024)
The Ukama Ustawi Scaling Fund is implemented through the CGIAR Regional Integrated Initiative on Diversification in East and Southern Africa. It is designed to accelerate the adoption of high-impact agricultural innovations. It serves as a platform for CGIAR and its partners to collaboratively develop, negotiate, and finance scaling strategies and action plans. In its initial round in 2024, the Fund awarded $125,000 to each of three innovation teams.